Práticas informacionais em grupos antivacina do Telegram: um estudo com sujeitos que não aderiram à vacinação contra COVID-19 - Carolina Costa Gonzaga (2023)
The COVID-19 pandemic enacted in 2020 culminated in the dissemination of excessive information and without clear sources of reference, triggering a dangerous phenomenon: misinformation. This phenomenon, in addition to the culture of believing in what is more convenient than what is established by science (post-truth culture), made the antivaccine movements consolidate even after a health crisis on the scale of the pandemic. Given the need to understand how the subject conforms to not adhering to the vaccination against COVID-19, this study aimed to studying it within the scope of Telegram’s anti-vaccine conversation groups. The cognitive bias present in the post-truth culture was identified as a factor inherent to their integration into such groups. The analysis of conversations based on these factors revealed that the informational practices of these subjects consist of interactions between information sources and vaccine meanings that the subjects themselves have, and these, in turn, affect the antivaccine culture in which they are immersed. These factors were understood as interdependent and essential informational practices for them to remain negligent about the vaccine in their bubbles.